Exploring gaps in young tourists’ travel experiences: a phenomenological approach - Atasoy, Burak; Türkay, Oğuz (Anais Brasileiros de Estudos Turísticos, 2025)
Although it has gained significant popularity in the literature, there is limited information on the behaviour of young tourists. This study addresses this gap by exploring how young tourists’ perceptions of their experiences are shaped and identifying the factors that influence their holidays. Furthermore, insights into youth tourism can inform the development of successful strategies by tourism destinations and managers. In this context, a phenomenological study was conducted to examine the relationship between planning, executing, and reflecting on a tourist trip. Qualitative data were obtained through document analysis, focus groups, and interviews. The results show that technology cannot be ignored when considering young people’s perceptions of tourism experiences. Technology and social media exert a dominant influence over all phases of young people’s travel planning and beyond. Moreover, different characteristics of young people, such as lifestyle, interests, expectations, and tourism behavior, are shaped by them. This inference necessitates a reevaluation of the approach to creating memorable tourism experiences proposed by Kim et al. (2012). This is because the factors in the expectation and perception process for young tourists are viewed differently from those of previous groups. As a result, tourism practitioners should shift their focus from experience quality to demographically based product and service design.